ChemInform Abstract: 1, 3‐Carbothiolation of 4‐(Trifluoromethyl)‐p‐quinols: A New Access to Functionalized (Trifluoromethyl)arenes. Issue 22 (3rd June 2014) - Liu, Xiao; Pan, Ling; Dong, Jinhuan; Xu, Xianxiu; Zhang, Qian; Liu, Qun
Abstract Treatment of the title substrate (I) with various ketene dithioacetals results in the formation of α‐arylated β‐ketothiolesters, nitriles, and carbonyl compounds via a tandem 1, 3‐carbothiolation/aromatization sequence.